SOCIO-PSYCHOLOGICAL EFFECTS OF INTERSPECIFIC INTERACTIONS IN A GROUP "HUMAN - PET" - A V Gagarin (Peoples' Friendship University of Russia (RUDN University), 2016)
The article reveals the features of interspecific interaction "Human - Pet" in aspects of psychology and behaviorism. This direction is shown to be promising in the theoretical and applied aspects. This is significant for the study of individual social activity and human life, as well as social groups. The article identifies the promising areas of the research of such interaction: in the development of family and child-parent relations; in the asocial individual development under the influence of various factors (social and personal); in various directions of media development (social advertising on television and in print), in fiction and film; in socially-significant communicating in social networks (communication through video sharing, etc.). It is shown that this perspective is important for research in education and upbringing. We have come to the conclusion that the problems are of social significance because the direct and/or indirect human contact with natural objects contributes to the development of different spheres of his/her personality (cognitive, communicative, aesthetic, ethical, emotional, volitional).